The Effects of Long-Term Treatment by Immunotherapy and Fluticazone on Broncial Hyperreactivity - G. Ilonidis; G. Anogianakis; Chr. Trakatelli; A. Anogeianaki; J. Giavazis; M. Trakatellis; I. Michalis (European Journal of Inflammation, 2003)
Thirty subjects (20 female and 10 male), all allergic to the mites D. Pteronyssinus and D. Farinae , participated in the present study which covered a period of four years. The subjects were randomly divided in two groups. Group I included 10 female and 5 male subjects, with an average age of 25.8 (+/− 3.5) years who received immunotherapy only. Group II had an average age of 31.5 (+/− 4) years and they received immunotherapy along with fluticazone propionate (1000mcg/day). The protocol for immunotherapy was the same for both groups. The basis FEV1 was determined for each subject of both Groups I and II and afterwards they were subjected to provocation tests of nebulized methacholine solution administered in consecutively larger concentrations until a drop in FEV1 >20 % (PC 20 ), was observed. Three years later, when their therapy was completed, all subjects were subjected to the same provocation test and a significant reduction in bronchial hyperactivity was documented for both groups. In particular, for Group I, the percentage of change in FEV1 values was 27.25 +/- 5.23 % and PC 20 5.11 +/− 2.64 mg/ml before immunotherapy, while after immunotherapy the same indicators were 22.22 +/- 7.08 % (P<0.05) and 6.85 +/− 4.03 mg/ml, (P<0.05) respectively. For Group II, the percentage of change in FEV1 values was 26.28 +/− 2.5 % and PC 20 5.42 +/− 2.5 mg/ml before immunotherapy, while after immunotherapy the same indicators were 12.27 +/- 2.49 % (P<0.01)and 11.64 +/− 5.14 mg/ml, P<0.01 respectively. It is concluded that although significant reduction in hyperreactivity can be achieved through immunotherapy, the combination of immunotherapy with daily fluticazone propionate administration shows the most promising results.